Numerical investigations and simulation of calcium distribution in the alpha-cell - Singh, Tejaswi; Vaishali, V.; Adlakha, Neeru (Fırat Evirgen, 2023)
The ?-cells are a part of islets of Langerhans located in the pancreas and are responsible for glucagon secretion. Calcium signaling is crucial for the regulation of the functions and structure of these ?-cells and the same is still not well understood. Here a mathematical model is framed to obtain more insights into calcium signaling in ?-cells. The non-linear reaction-diffusion equation for calcium signaling along with boundary conditions is employed to propose the model for a one-dimensional steady-state case. The numerical solutions were obtained using the Newton-Raphson method and the cubic spline method. The combination of Newton-Raphson and cubic spline has proved to be quite effective in numerical simulations and in generating deeper insights into calcium regulation in an ?-cell under various conditions. The results provide information about changes in source influx, buffers, ER leak, and SERCA pump leading to disturbances in calcium homeostasis, which can be responsible for the development of diabetes and other metabolic disorders.
Keywords: Biological Mathematics; Biyolojik Matematik; Applied Mathematics (Other); Uygulamalı Matematik (Diğer)